Preparedness and Understanding Required for the Attainment of Foundational Numeracy in India - Gandhi, Haneet (Voices of Teachers and Teacher Educators, 2021)
With the announcement of the National Education Policy 2020, several new structures and concerns in the Indian education system got highlighted. One such concern is on strengthening the mathematical abilities of citizens of India. The policy emphasizes on the development of mathematical skills from early years onwards. This paper takes cognizance of the urgency related to the development of ‘foundational numeracy’ and proposes introducing ‘bhaashayi ganit’ in the foundational years. Talking mathematics in a contextualised manner through stories may help strengthen foundational literacy and numeracy. The article also shares the sensitivity required for understanding the term ‘numeracy’ beyond numerical know-how and its relevance in developing favourable mathematical dispositions.